9514 1404 393
Answer:
A. (3, 3)
Explanation:
The coefficients of y are opposites, so adding the two equations will eliminate y.
(x +2y) +(3x -2y) = (9) +(3)
4x = 12 . . . simplify
x = 3 . . . . . divide by 4
Using the first equation, we can find y:
3 +2y = 9 . . . . . .substitute for x
2y = 6 . . . . . . . . subtract 3
y = 3 . . . . . . . . . . divide by 2
The solution is (x, y) = (3, 3).
_____
Additional comment
For this problem, it is easy to just try the answers. You don't have to go far to show the first answer (A) satisfies both equations.
3 + 2(3) = 9; 3(3) -2(3) = 3